Virologic outcomes of HIV-infected children undergoing a single-class drug substitution from Lopinavir/Ritonavir- to Efavirenz-based antiretroviral treatment: A retrospective cohort study - Reichmuth, Kirsten Leah (Department of Public Health and Family Medicine, 2015)
Major advances have been made in preventing mother to child transmission of HIV (PMTCT), as well as in decreasing morbidity and mortality amongst HIV-infected infants and children. However, maintenance of excellent adherence to combination antiretroviral therapy (cART) lifelong is required to achieve optimal benefits. In addition, treatment options for children are limited by potential drug-resistance following PMTCT exposure, availability of appropriate and palatable formulations, long-term toxicity concerns and drug-interactions - notably with co-treatment for tuberculosis. Given these challenges, drug simplification strategies for children remains an important area of research. The World Health Organisation (WHO) recommends lopinavir/ritonavir-based (LPV/r) cART as first-line for children <36 months old with the option to substitute LPV/r with a non-nucleoside reverse transcriptase inhibitor if virologic suppression is maintained. This simplification strategy is potentially cost-saving, regimen-sparing and more tolerable, with a better long-term side-effect profile. Consequently, benefits should also exist in terms of adherence. The main evidence in support of this strategy has come from trials conducted by the Nevirapine Resistance Studies (NEVEREST) group. In particular, the NEVEREST 3 trial showed that substituting LPV/r for efavirenz (EFV) in children aged 36-60 months virologically suppressed on LPV/r-based cART was protective against viral rebound and had no effect on virological failure compared with remaining on LPV/r. To our knowledge, no studies to date have examined the virologic outcomes of children changed to an EFV-based regimen after initiating a LPV/r based regimen in routine, resource-constrained settings where selection of patients as eligible for EFV substitution and subsequent monitoring practices may be less rigorous than in a trial setting. At the International Epidemiologic Database to Evaluate AIDS - Southern Africa collaboration's (IeDEA-SA) South African sites LPV/r has been used for first-line cART in children <36 months of age irrespective of PMTCT antiretroviral exposure. At many of these sites clinicians have, at their discretion, elected to substitute LPV/r with EFV when children reach 36 months of age. This has provided the opportunity to conduct an observational study to investigate this practice in a routine-care setting â€“ comparing outcomes in children virologically suppressed and â‰¥36 months old who underwent a substitution of LPV/r to EFV (substitution group) to those who remained on their initial LPV/r-based regimen (stay group).